International journal of Asian business and information management (IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2010)
The International Journal of Asian Business and Information Management (IJABIM) provides timely and in-depth analysis on the globalization and sustained development of Asian commerce and management technologies with a clear international and interdisciplinary approach. A comprehensive resource for policy makers, government officials, academicians, and practitioners, this journal contains a wealth of valuable research on theories and practices which underpin successful business and management in Asia.